Conceptualisation of an Environment for the Development of Simulators based on the Finite Element Method - Lencastre Pinheiro de Menezes e Cruz, Maria (2004)
In this work we address the conceptualisation of a Simulation Environment for the development of multi-physic simulators based on the Finite Element Method (FEM). Simulators are economical means of understanding and evaluating the performance of abstract and real-world systems. Our simulation perspective is the class of simulations for phenomena represented by a set of functions distributed in space and possibly in time, whose behaviour is based on the FEM. The importance of these simulators has to do with the effectiveness of the FEM, a general-purpose numerical method, which can easily be developed to analyse and solve various kinds of problems frequently found in human daily life, and in its power to provide accuracy and reliability in the solution of partial differential equations. FEM Simulations consider systems of possibly millions of algebraic equations, numerical integrations, mesh generations, matrix and vector manipulations, solutions of linear and non-linear systems, and so on. These features undoubtly justify the development of a specific computational environment. This work emphasizes the adaptation of software engineering practices and methodologies for organizing and reusing the specific domain of simulators formulated using the FEM. The work defines an environment and its architecture for the development of simulators. It also proposes some specific patterns for solving relevant problems of our domain of knowledge, and describes their application through a case study.